The Dynamics of Contemporary Islamic Thought: Between Traditionalism and Reform in the Context of Globalization - Abbas Tekeng; Sulaiman Ibrahim (Pascasarjana IAIN Sultan Amai Gorontalo, 2025)
Globalization has brought significant structural changes to the way Muslims understand, interpret, and articulate religious teachings in the contemporary public sphere. Contemporary Islamic thought is caught in a continuous tension between traditionalism, which emphasizes the continuity of classical scholarly authority, and reformism, which encourages contextual reinterpretation of normative Islamic texts. This article aims to analyze these dynamics by highlighting hermeneutic aspects, the transformation of religious authority, and responses to global issues such as democracy, human rights, and gender. This study uses a qualitative approach through a systematic literature review of the latest academic literature. The results show that the tension between traditionalism and reform has not produced a stable epistemological synthesis, thus requiring an integrative framework based on maqasid al-shariah and collective ijtihad to maintain the relevance of Islam in the global context without losing its traditional legitimacy.